PROSEDUR PENGEMBANGAN BAHAN AJAR PENDIDIKAN AGAMA ISLAM (PAI) - Atang Suharna; Maslani; Ade Andriyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article aims to discuss the procedures for developing PAI teaching materials. The literature review research method was used to understand key concepts and best practices in developing PAI teaching materials. The main data sources include literature from the fields of Islamic Religious Education and educational psychology, as well as the views of educational practitioners involved in the development process. Data collection techniques include searching, selecting and analyzing relevant literature to formulate a comprehensive framework for compiling effective PAI teaching materials. The results of the systematic and comprehensive development of Islamic Religious Education (PAI) teaching materials show a significant increase in students' motivation and understanding of the material. The discussion in this article highlights that teaching materials that are designed in an attractive and easy to understand manner can facilitate a more effective learning process. It was also stated that the stages of needs analysis, design, development, implementation and evaluation are a systematic approach that is crucial in creating responsive and relevant teaching materials. The importance of understanding the local context and characteristics of students is emphasized as an essential factor in ensuring the success of developing teaching materials. Continuous evaluation of the teaching materials that have been developed is necessary for adaptation and quality improvement according to practical feedback. In conclusion, the development of effective PAI teaching materials not only supports students' learning needs but also strengthens teachers' capacity to deliver the material efficiently.